2016
DOI: 10.17352/2455-2968.000033
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Rate of Post-Operative Anastomotic Leak Following Colorectal Resection Surgery: A Systematic Review

Abstract: Purpose: Anastomotic leak following colorectal resection surgery is associated with short and long-term negative patient outcomes, prolonged hospitalization, and increased healthcare costs. Various patient related and surgical factors are known to contribute to the development of postoperative anastomotic leaks. This study systematically reviewed the literature to assess the incidence of post-operative leak and identify patient factors associated with the development of leaks. Methods:Articles published from 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…An anastomotic leak (AL) is one of the most serious surgical complications that can develop following colorectal surgery [1]. In two recent systematic reviews, the AL rate varied from 4% to 9% [2, 3]. In the review that considered only low anterior resection (LAR) studies, the pooled overall rate of AL was found to be 8.88% [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An anastomotic leak (AL) is one of the most serious surgical complications that can develop following colorectal surgery [1]. In two recent systematic reviews, the AL rate varied from 4% to 9% [2, 3]. In the review that considered only low anterior resection (LAR) studies, the pooled overall rate of AL was found to be 8.88% [3].…”
Section: Introductionmentioning
confidence: 99%
“…In two recent systematic reviews, the AL rate varied from 4% to 9% [2, 3]. In the review that considered only low anterior resection (LAR) studies, the pooled overall rate of AL was found to be 8.88% [3]. Several risk factors for the occurrence of AL have been identified, including male sex, diabetes mellitus, use of tobacco, blood loss, perioperative transfusion, operative time, preoperative chemoradiation, previous abdominal surgery, and emergency surgery [317].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reflects practical experience in that most leaks are detected during the first 10 days after surgery and, thus, close monitoring of patients is required during this period in order to detect complications as early as possible [19, 28]. In this study, the intraoperative creation of a new anastomosis after a leak during surgery appeared to increase the patients' risk of a postoperative leak compared to estimates in the literature [12]. However, these findings have to be interpreted with caution owing to the inclusion criteria of the incidence of intraoperative leaks and the low overall number of subjects with postoperative leaks.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, the evidence suggests that laparoscopic surgery may be advantageous compared to open surgery [410]. In particular, postoperative anastomotic leaks have been found to occur less frequently after laparoscopic surgery than after open surgery [11, 12]. However, these findings remain controversial, as other studies did not observe a significant advantage of laparoscopic versus open surgery or of stapled versus sutured anastomoses [1318].…”
Section: Introductionmentioning
confidence: 99%